Indigenous peoples' rights under international law - Te Aho, Fleur (The New Zealand Yearbook of International Law, 2015)
This note reviews New Zealand's state practice regarding Indigenous peoples' rights under international law in 2015 and traces key international developments concerning those rights. In 2015 New Zealand demonstrated support for efforts to improve Indigenous participation in the United Nations (UN) and extend the mandate of the UN Expert Mechanism on the Rights of Indigenous Peoples (EMRIP) to advance implementation of the UN Declaration on the Rights of Indigenous Peoples (UNDRIP). But it indicated that - domestically - the UNDRIP would be implemented within existing legal and constitutional arrangements. There were several noteworthy developments regarding Indigenous peoples' rights during the year. Indigenous peoples and their rights received limited reference in the 2030 Agenda for Sustainable Development agreed by the UN General Assembly (GA) and in the Paris Agreement negotiated under the auspices of the UN Framework Convention on Climate Change (UNFCCC). Nationally, draft bills proposing significant changes to the law governing Māori land and te reo Maori (the Maori language) were released, which will contribute to growing jurisprudence in these areas. In November the text of the Trans-Pacific Partnership (TPP) was made public, which includes an exception clause on the Treaty of Waitangi (Treaty). The UN Committee against Torture (CAT) and the UN Working Group on Arbitrary Detention (WGAD) commented on the human rights situation of Māori. The GA, the UN Human Rights Council (HRC), international human rights treaty monitoring bodies and others also devoted attention to Indigenous peoples' rights in the course of their work.
Keywords: Children's rights; Maori (New Zealand people)–Criminal justice system; New Zealand; Permanent Forum on Indigenous Issues (United Nations); United Nations. Human Rights Committee

E-Whanaungatanga: The role of social media in Māori political empowerment - Waitoa, Joanne; Scheyvens, Regina; Warren, Te Rina (AlterNative: An International Journal of Indigenous Peoples, 2015)
Lower voter turnout and lack of political empowerment sees Māori engaging less than Pākehā (European New Zealanders) with the political system to the detriment of Māori development. This paper explores the potential of social media to enhance Māori development via political engagement. Mana Party Facebook pages are used as a case study to investigate if social media can encourage Māori political awareness and participation. Results found that social media has both positive and negative implications for political engagement and indigenous development. While social media aligns with tikanga Māori (values/customs) through tino rangatiratanga (self-determination) and whanaungatanga (relationships/networks), other aspects such as cultural misappropriation conflict with Māori values. The paper explores tensions in the use of social media for political engagement among indigenous peoples and offers a framework promoting e-whanaungatanga to illustrate how they might use social media in a way that emphasizes the positive and mitigates the negative aspects of the platform.

Mātauranga Māori, tino rangatiratanga and the future of New Zealand science - Broughton, D; McBreen, K (Journal of the Royal Society of New Zealand, 2015)
All peoples develop their own academic traditions: philosophies grounded in their experiences over successive generations, and theories for growing knowledge and wisdom. Mātauranga Māori (mātauranga) is the Indigenous knowledge system of these lands. It is dynamic, innovative and generative. The mātauranga continuum is the knowledge accumulated through this system. Government policies and systems have marginalised mātauranga and prioritised Western science, and the past 100 years have seen a slowing in the expansion of the mātauranga continuum. Unless the survival of mātauranga is prioritised, it will cease to flourish. Māori have discussed and written extensively about the ongoing impact of colonisation on mātauranga and tikanga Māori. This paper builds on those discussions, arguing for tino rangatiratanga, including Māori ownership of mātauranga, fulfilment of the government's obligations to Māori, and the reinstitution of mātauranga as a primary knowledge system in Aotearoa. It explains why mātauranga revitalisation is important and outlines some of the steps towards this goal. We are calling for Western academics to support mātauranga revitalisation, with the vision of two functional knowledge systems operating that are unique to New Zealand.
Keywords: mātauranga māori; self-determination; tino rangatiratanga

Maori rights: legal or political? - Charters, Claire (Public law review (North Ryde, N.S.W.), 2015)
Willingness of New Zealand courts to enforce legal rights where a political mechanism to address Maori rights exists - land rights - human rights - political rights - principles of the Treaty of Waitangi - takanga.
Keywords: crown law; human rights; land rights

Neo-Liberal Settlements: From Adam Smith to Treaty Settlements - Tau, Te Maire (NZ Journal of History, 2015)
Keywords: kāwanatanga; sovereignty; treaty settlements

‘Ka Hoki A Kupe?’: The Political Career of Matiu Rata, 1963–1979 - McDowell, Tiopira (New Zealand Journal of History, 2015)

Taua nakahi nui: Maori, liquor and land loss in the 19th century - McDowell, Tiopira (AlterNative : an international journal of indigenous peoples, 2015)
This article outlines the fraudulent practices of settler traders and land agents who employed alcohol to facilitate the alienation of Maori lands, highlighting the close relationship between Maori, liquor and land loss in 19th century New Zealand. Traders and agents developed a range of strategies, forged in Britain, tempered by colonial experience and wielded with deft precision in New Zealand to defraud Maori of their lands. Government efforts to pre-empt and prevent the worst excesses of settler crime proved ineffectual, self-defeating, paternalistic and ultimately unenforceable. Maori came to regard settler practices, the successive failure of legislation to alleviate the problem, and state connections with the liquor industry to be part of a thinly veiled conspiracy to destabilize their communities and alienate their lands. While this conclusion is highly problematic, it is likely that traders and agents had witnessed or were aware of similar practices in the settler colonies of Australia, Canada and North America, and made good use of them in New Zealand to access Maori lands.
Keywords: alcohol; colonies; crown policy; government relations; land loss; land tenure; race relations

First Nations, Maori, American Indians, and Native Hawaiians as Sovereigns: EAP with Indigenous Nations Within Nations - Haring, Rodney C.; Hudson, Māui; Erickson, Louisa; Taualii, Maile; Freeman, Bonnie (Journal of Workplace Behavioral Health, 2015)
Indigenous workforces have existed across the world since the creation of Earth. What has changed is the evolution of multicultural societies, governments, and landscapes that have become part of, or sit parallel to, sovereign Indigenous nations and their workforces. An international response to Employee Assistance Programming (EAP) and workplace health will be shared from various Indigenous groups across the globe. These societies include the Maori of New Zealand, First Nations of Canada, American Indian groups from the U.S. mainland, and Native Hawaiians. Guidelines for EAP practice include the discussion of historical trauma, communication skills, confidentiality, and environmental issues. Theoretical underpinnings for health sovereignty are shared through ancient teachings of Indigenous philosophies and their relationships to contemporary EAP development and utilization.
Keywords: indigenous data sovereignty; native americans

Indigenous ‘stakeholders’? Theorising external citizenship rights for Māori in Australia - West, Kiri (MAI Journal 2015, 2015)

Recognition and indigenizing official statistics: Reflections from Aotearoa New Zealand and Australia - Kukutai, Tahu; Walter, Maggie (Statistical Journal of the IAOS, 2015)
In First World colonised nations such as Aotearoa New Zealand and Australia, population statistics form the evidentiary base for how Indigenous peoples are known and `managed' through state policy approaches. Yet, population statistics are not a neut
Keywords: colonisation; crown policy; data sovereignty; identity; policy; self-determination; statistics